Effect of selective serotonin reuptake inhibitor discontinuation on anxiety-like behaviours in mice. (July 2022) - Collins, Helen M; Pinacho, Raquel; Ozdemir, Dersu; Bannerman, David M; Sharp, Trevor
Background: Abrupt cessation of therapy with a selective serotonin reuptake inhibitor (SSRI) is associated with a discontinuation syndrome, typified by numerous disabling symptoms, including anxiety. Surprisingly, little is known of the behavioural effect of SSRI discontinuation in animals. Aim: Here, the effect of SSRI discontinuation on anxiety-like behaviour was systematically investigated in mice. Methods: Experiments were based on a three-arm experimental design comprising saline, continued SSRI and discontinued SSRI. Mice were assessed 2 days after SSRI discontinuation over a 5-day period using the elevated plus maze (EPM) and other anxiety tests. Results: An exploratory experiment found cessation of paroxetine (12 days) was associated with decreased open-arm exploration and reduced total distance travelled, in male but not female mice. Follow-up studies confirmed a discontinuation effect on the EPM in male mice after paroxetine (12 days) and also citalopram (12 days). Mice receiving continued paroxetine (but not citalopram) also showed decreased open-arm exploration but this was dissociable from the effects of discontinuation. The discontinuation response to paroxetine did not strengthen after 28 days of treatment but was absent after 7 days of treatment. A discontinuation response was not discernible in other anxiety and fear-learning tests applied 3–5 days after treatment cessation. Finally, discontinuation effects on the EPM were typically associated with decreased locomotion on the test. However, separate locomotor testing implicated anxiety-provoked behavioural inhibition rather than a general reduction in motor activity. Conclusion: Overall, this study provides evidence for a short-lasting behavioural discontinuation response to cessation of SSRI treatment in mice.